2020
DOI: 10.21203/rs.3.rs-51751/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Poorer Nutritional Status Impacts Quality of Life in a Sample Population of Elderly Cancer Patients

Abstract: Rationale: Quality of Life (QoL) is impaired in cancer, and the elderly are particularly vulnerable to malnutrition. A diagnosis of cancer in elderly patients further exacerbate risks of negative health outcomes. Here we investigated associations between QoL and nutritional status in a sample population of mostly socially deprived elderly cancer patients.Method: 432 patients with diagnosed cancer were recruited for this cross-sectional study at point of admission to a tertiary referral charitable hospital for … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…30 Some individuals still reported fatigue and difficulties in performing daily activities 6 months after hospital discharge and rehabilitation. 29,36 According to Rios and colleagues 48 and Rives-Lange, 49 malnutrition is a possible contributor to low QoL during long COVID. The relationship between QoL and nutritional status has been previously investigated in other conditions and is associated with impaired functional status and delayed recovery.…”
Section: Discussionmentioning
confidence: 99%
“…30 Some individuals still reported fatigue and difficulties in performing daily activities 6 months after hospital discharge and rehabilitation. 29,36 According to Rios and colleagues 48 and Rives-Lange, 49 malnutrition is a possible contributor to low QoL during long COVID. The relationship between QoL and nutritional status has been previously investigated in other conditions and is associated with impaired functional status and delayed recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Among hospitalized cancer patients, malnutrition tends to worsen during hospital stays [3,4]. It has been associated with a greater risk of complications [5], longer hospital stays [6], poorer tolerance and response to treatments [7], shorter survival [8,9], and a significant decline in health-related quality of life [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition possesses a negative impact on the quality of life of cancer patients [4,5]. It is demonstrated that malnutrition is an independent predictor of poor quality of life in cancer patients on several levels: physical, functional, emotional, and social [5,6]. For instance, malnutrition was correlated with poor physical functioning in oral or oropharyngeal cancer patients [7].…”
Section: Introductionmentioning
confidence: 99%